Development of Domia Card (Domino Chemistry) as Evaluation Media of Mol Concept - Anastasius Khristozolla Phikly; Andi Ifriany Harun; HUsna Amalya Melati (Universitas Pendidikan Mandalika, 2023)
The level of achievement of students at State Senior High School (SMAN) 1 Putussibau in the material of the mole concept only reached 20%, and this figure cannot even depict the true potential of students in understanding the mole concept due to indications of cheating in every monotonous evaluation. DOMIA (Chemical Domino) was developed to address the problem of a lack of variation in evaluations while also reducing the incidence of student cheating in the evaluation process. DOMIA was developed with the R&D principle using the ADDIE model, and each process will be revised according to needs and field findings. The development of DOMIA took place after the needs analysis process through direct interviews with subject teachers and several randomly selected students. The developed DOMIA was then validated to test the level of feasibility and reliability based on Guilford indicators as a reference in assessment. DOMIA has Kr = 0.97 and Ks = 0.947, indicating that DOMIA is highly valid and very reliable, making it ready for implementation and serving as a new evaluation tool that has not existed in the chemistry subject before.